Trainspotting (Mark Renton #2) - Irvine Welsh (Vintage, 1994)
The bestselling novel by Irvine Welsh that provided the inspiration for Danny Boyle's hit film. Choose us. Choose life. Choose mortgage payments; choose washing machines; choose cars; choose sitting oan a couch watching mind-numbing and spirit-crushing game shows, stuffing fuckin junk food intae yir mooth. Choose rotting away, pishing and shiteing yersel in a home, a total fuckin embarrassment tae the selfish, fucked-up brats ye've produced. Choose life.
Keywords: Fiction; Classics; Thriller; Mystery; Dark